Kaiser Franz Joseph – eine Institution. Der kaiserliche Geburtstag im Spiegel der CAZ und der NFP in den Jahren 1903–1914. - Ricarda Hofer (Historia.scribere)
The following introductory seminar paper fans out the perception of Emperor Francis Joseph I. and his reign in two regions of the Cisleithanian part of the k.u.k. Monarchy at the dawn of the 20th century. In this closing epoch of the Empire, the perceptions of the relationship between the Emperor and his various german-speaking peoples can be reflected exemplarily by articles published in occasion of the emperor’s birthday on August 18th; the Czernowitzer Allgemeine Zeitung and the Neue Freie Presse reveal an interesting insight to the contemporary reception of the dying Monarchy and this emperor, who seemed to stiffen in his function in order to protect the declining glow of his family’s heritage – an attitude which was laid out in heroizing as well as critical views, as this paper will show hereafter.